FAKTOR - FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL EMITEN SEKTOR MANUFAKTUR DI BEI PERIODE 2006 – 2011 - Retnaningrum, Maharani (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2012)
This research was performed to investigate the influence of profitability, firm size, growth, asset structure, and liquidity on capital structure at manufacture company published financial report during period 2006 - 2011. Empirical evidence showed that profitability, firm size, and liquidity had significant influence on capital structure of manufacture company listed in ISX over period 2006-2011 at level of significance less than 5%.